2022
DOI: 10.1007/s00265-022-03135-3
|View full text |Cite
|
Sign up to set email alerts
|

Detecting behavioural lateralisation in Poecilia reticulata is strongly dependent on experimental design

Abstract: Despite the potential benefits gained from behavioural lateralisation, defined as the asymmetrical expression of cognitive functioning, this trait demonstrates widespread variation within and between populations. Numerous methodologies have been applied to investigate lateralisation, although whether different methodologies give consistent results has been relatively understudied. In this study, we assess (1) the repeatability of individual Poecilia reticulata’s lateralisation indexes between a classic detour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The reason our results differ from some previous publications could be due to such differences, or it could be due to the relatively small sample sizes from some of the river systems, or differences between studies in number of turns the fish were run in the lateralization arena. It has recently been shown that lateralization can be easily affected by experimental setup and it can have low repeatability (Clark et al, 2020; Penry‐Williams et al, 2022; Roche et al, 2020; Sundin & Jutfelt, 2016). This was also found here, where the crack in the glass arena used in the first lateralization test (not included in the analyses) led to an unintended but strong preference for that side (Figure S2A).…”
Section: Discussionmentioning
confidence: 99%
“…The reason our results differ from some previous publications could be due to such differences, or it could be due to the relatively small sample sizes from some of the river systems, or differences between studies in number of turns the fish were run in the lateralization arena. It has recently been shown that lateralization can be easily affected by experimental setup and it can have low repeatability (Clark et al, 2020; Penry‐Williams et al, 2022; Roche et al, 2020; Sundin & Jutfelt, 2016). This was also found here, where the crack in the glass arena used in the first lateralization test (not included in the analyses) led to an unintended but strong preference for that side (Figure S2A).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of lateralization use indices to demonstrate individuals differ in their lateralization. However, these indices do not account for the fact that behavioural traits might be affected by environmental conditions [ 21 , 22 ]. Thus, we used repeatability analyses to show that individuals repeatably rolled to the left or right ( R = 0.87) in a mixed model analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indices have been used to determine lateralization in species including humans [ 15 ], killer whales Orcinus orca [ 16 ], and birds of prey [ 17 ]. However, observed lateralization could be caused by poor experimental design or by temporary environmental effects that change any given behaviour (such as weather [ 18 ], time of day [ 19 ], or location [ 20 ]), rather than intrinsic and consistent among-individual differences over time [ 21 , 22 ]. Repeatability analyses are now widely used in behavioural studies [ 23 , 24 ] and address this by estimating, on a scale of 0–1 (from no to perfect repeatability), how individuals behaviourally differ from one another, over two or more independent sample periods.…”
Section: Introductionmentioning
confidence: 99%